ANALISIS KERAGAMAN GENETIK Musa balbisiana Colla BERDASARKAN MARKA RAPD DAN ISSR [Genetic variation analyses of Musa balbisiana Colla based on RAPD and ISSR markers] - Poerba, Yuyu Suryasari; Ahmad, Fajarudin (Research Center for Biology-Indonesian Institute of Sciences, 2013)
Wild Musa balbisiana Colla is one of the progenitors of cultivated bananas and plantains. It is originated in Asia, and distributed from India to Papua New Guinea. This study was conducted to assess the molecular diversity of 25 accessions of M. balbisiana based on Random Amplified Polymorphic DNA (RAPD) and Inter Simple Sequence Repeats (ISSR) analyses. RAPD and ISSR fingerprints of these banana varieties were detected by amplifications of nine primers of RAPDs and six primers of ISSRs. RAPD primers produced 84 amplified fragments varying from 150 bp to 2300 bp in size. 21.43 % of the amplification bands were polymorphic. ISSR primers produced 61 amplified fragments varying from 250 bp to 2200 bp in size. 29.30 % of the amplification bands were polymorphic. Based on these results, the 25 accessions of Indonesian M. balbisiana showed a low genetic variation, with coefficient of similarity ranged from 0.81 to 0.99.